Pengaruh Likuiditas dan Ukuran Perusahaan Terhadap Return Saham pada Sektor Energi yang Terdaftar di Bursa Efek Indonesia - Ratna Sari; Muhammad Iqbal Pribadi; Rahman Anshari (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
This study aims to examine the effect of liquidity, proxied by the Current Ratio, and firm size, proxied by Total Assets, on stock returns. The research period covers the years 2019–2023. The population of this study includes financial reports of 90 energy sector companies listed on the Indonesia Stock Exchange. A purposive sampling technique was employed, resulting in 46 selected companies as the sample. The study uses secondary data derived from the annual financial reports of energy sector companies for the 2019–2023 period. The data analysis method used in this study is panel data regression analysis. In this research, liquidity is measured using the Current Ratio (CR), while firm size is measured by Total Assets. The results indicate that liquidity has a negative and significant effect on stock returns, whereas firm size has a negative but not significant effect on stock returns.